-x+3+2x=0

Simple and best practice solution for -x+3+2x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+3+2x=0 equation:


Simplifying
-1x + 3 + 2x = 0

Reorder the terms:
3 + -1x + 2x = 0

Combine like terms: -1x + 2x = 1x
3 + 1x = 0

Solving
3 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 1x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 0 + -3
1x = 0 + -3

Combine like terms: 0 + -3 = -3
1x = -3

Divide each side by '1'.
x = -3

Simplifying
x = -3

See similar equations:

| (1+.05)2= | | -21v=5 | | 4(2x-6)=3x-27 | | (x+6)2=49 | | (3x+5)(5x-7)=0 | | 1/6(2x-2)=7 | | -9+y=4 | | y=2(-3)-6 | | 5x^2-8x=10 | | 4=6+v | | 8x-73=-8x+7 | | 5y^2+12=7y | | y^2=3y+10 | | 8x^2-2=286 | | .06+.12(4x+50000)=87000 | | 9(2x-4)1/2+2=38 | | m^2-50=5m | | 5=1q+7 | | 5(4-2x)=30 | | 6y^2+10=4y | | 8x^2+3x+1=0 | | y^2=6y+27 | | 7(3x+1)=5x-6x | | y^2=6+27 | | x+.15x=4623 | | 2s-3s=65 | | 2x+5/3=9 | | 10x+1=491 | | (x^2)-(10x)+(45)=0 | | 18+99+z=180 | | x(.15)=4623 | | 46=-2(m+4)+m |

Equations solver categories